Políticas Públicas para internet en América Latina y El Caribe - Bonilla Soria, Paul (Cuadernos de Administración, 2003)
The first section of this paper presents the general characteristics of Lain American and Caribbean public policy. It begins with an introduction that states its contemporary orientations from a conceptual perspective which relate them to the development process implemented in the region. It is also introduced the civil society organizations (CSO) approche to this issue in which the stress is on population needs satisfactions. The sccond section, states the relationship between telecommunications and Value Added Services. Since 1990 until now they have gone through a process of technological and enterpreneurial modernization which, in the last meant their privatizations in most of the countries althought there are exception! that confirm the structural diversity that characterized the continent identity. The third section describes the growth process of the Internet in the region. A characterizations of the digital gap is made comparing our continent and the developped countries by means of indicators that confirm this situations. The contextual elements presented in the prévins sections explain the public policy characteristics for internet which have been identified in the present moment. Concepts and references values that become objectives and goals to reach in different countries acknowledge their specificities, Finally, concret activities that public policies implement in the field of legislations, technological modernizations and connectivity process are presented.